Advances in Nucleoside and Nucleotide Analogues in Tackling Human Immunodeficiency Virus and Hepatitis Virus Infections. (12th February 2021) - Ramesh, Deepthi; Vijayakumar, Balaji Gowrivel; Kannan, Tharanikkarasu
Abstract: Nucleoside and nucleotide analogues are structurally similar antimetabolites and are promising small‐molecule chemotherapeutic agents against various infectious DNA and RNA viruses. To date, these analogues have not been documented in‐depth as anti‐human immunodeficiency virus (HIV) and anti‐hepatitis virus agents, these are at various stages of testing ranging from pre‐clinical, to those withdrawn from trials, or those that are approved as drugs. Hence, in this review, the importance of these analogues in tackling HIV and hepatitis virus infections is discussed with a focus on the viral genome and the mechanism of action of these analogues, both in a mutually exclusive manner and their role in HIV/hepatitis coinfection. This review encompasses nucleoside and nucleotide analogues from 1987 onwards, starting with the first nucleoside analogue, zidovudine, and going on to those in current clinical trials and even the drugs that have been withdrawn. This review also sheds light on the prospects of these nucleoside analogues in clinical trials as a treatment option for the COVID‐19 pandemic. Abstract : Either/or, or both ? In this review, nucleoside and nucleotide analogues are considered as drugs. Their status in clinical trials and mechanisms of action for HIV and hepatitis are examined with respect to their viral genomes and the drugs′ action against them. Drugs to counter coinfection are also discussed as is the possible repurposing of these drugs.